2016
DOI: 10.1111/eos.12271
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity pulsed ultrasound accelerates nerve regeneration following inferior alveolar nerve transection in rats

Abstract: Inferior alveolar nerve (IAN) injury, which is frequently caused by orofacial surgery or trauma, induces sensory loss in orofacial regions innervated by the IAN. However, no effective treatment for orofacial sensory loss currently exists. We determined whether sensory loss in facial skin above the mental foramen following IAN transection was recovered by exposure of the transected IAN to low-intensity pulsed ultrasound (LIPUS). Inferior alveolar nerve transection (IANX) was performed in 7-wk-old male Sprague-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…FDA-approved ultrasound therapy devices for bone healing stimulation provide low ultrasound intensities of 30 mW/cm 2 and 1.5 MHz frequency. Identical transducer parameters have recently been proven to enhance the morphological and functional regeneration of sensory nerves in an experimental nerve injury model (28). However, none of these already clinically available ultrasound transducers has been investigated for peripheral nerve injuries yet.…”
Section: Discussionmentioning
confidence: 99%
“…FDA-approved ultrasound therapy devices for bone healing stimulation provide low ultrasound intensities of 30 mW/cm 2 and 1.5 MHz frequency. Identical transducer parameters have recently been proven to enhance the morphological and functional regeneration of sensory nerves in an experimental nerve injury model (28). However, none of these already clinically available ultrasound transducers has been investigated for peripheral nerve injuries yet.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies assessed nerve regeneration in rats. Sato et al (2016) described a possible novel therapy for inferior alveolar nerve injury, frequently caused by trauma or surgery, using a daily treatment LIPUS protocol [ 118 ]. More recently, Xia et al (2019) described the effects of LIPUS combined with iPSC-NCSC, perfluorotributylamine, and growth differentiation factor 5 for the repair of peripheral nerve injury [ 81 ].…”
Section: Therapeutic Applications Of Ultrasoundmentioning
confidence: 99%
“…In vitro study demonstrated that nerve growth factor (NGF) combined with low-intensity pulsed ultrasound (LIPUS) stimulation may have some effects on PC12 cell neurite outgrowth ( Zhao et al, 2016 ). Moreover, transected inferior alveolar nerve with LIPUS facilitated morphological and functional regeneration which suggested the potentiation of LIPUS as a novel therapy for PNS injury ( Sato et al, 2016 ). Even without growth factor combination, the ultrasound was able to accelerate autograft nerve regeneration at energy of 250 mW/cm 2 ( Jiang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%